2014
DOI: 10.5704/moj.1411.002
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis in Elderly Patients following Surgery for Fracture of the Proximal Femur

Abstract: The incidence of Deep Vein Thrombosis (DVT) is high in orthopaedic cases, associated with morbidity and mortality. This study was done to evaluate the incidence of DVT and factors that contributed to DVT in elderly patients with proximal femur fracture who underwent surgery. Patients 60 years of age and older with proximal femur fracture who underwent surgery were enrolled into this study. Daily observation of the clinical signs of DVT was done post operatively until the subjects were discharged from the hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In previously published literature, the distribution of DVT in lower extremity fractures was studied. Some authors concluded that hip fractures presented with a highest incidence of 17-58% 6 , the incidence in distal femur fractures treated surgically was 25% 7 , and in foot and ankle surgery was 2.1%. 3 It seems that DVT may occur more often in the proximal fracture of lower extremity, and we speculate that fracture site may be correlated closely with the incidence of DVT in lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…In previously published literature, the distribution of DVT in lower extremity fractures was studied. Some authors concluded that hip fractures presented with a highest incidence of 17-58% 6 , the incidence in distal femur fractures treated surgically was 25% 7 , and in foot and ankle surgery was 2.1%. 3 It seems that DVT may occur more often in the proximal fracture of lower extremity, and we speculate that fracture site may be correlated closely with the incidence of DVT in lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, another study on elderly patients reported that the prevalence of asymptomatic DVT on admission and the incidence during hospital follow up were respectively 5.5% and 2.6 per 1,000 person-days, the prevalence and the incidence reached respectively 17.8% and 6.0 per 1,000 person-days among patients over 80 years ( 11 ). Also, a study in Indonesia ( 12 ) reported (42.86 %) as prevalence of DVT among elderly patients. According to the results of our study, no significant association was observed between gender and the development of DVT among elderlies.…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that D-dimer levels above 0.5 ug/ml at admission were associated with a 47% increased risk of DVT, which was comparable to the ndings of Zhang et al [10] study of lower extremity fractures. D-dimer is a brin degradation marker that represents secondary brinolytic activity, hypercoagulability, and brinolytic activity in the blood, which has clinical value in the diagnosis of thrombus events [27]. Yamasaki et al [28] retrospectively collected 588 patients undergoing lumbar spine surgery and found that the risk of DVT increased by 9% with D-dimer greater than 19.2 ug/ml one week after surgery.…”
Section: Discussionmentioning
confidence: 99%